Experiences of violence at school from the stuttering patients’ perspective - Marina Pelingrin Zamprogno; Patrícia Pupin Mandrá; Tatiane Cristina Gonçalves; Tatiane Martins Jorge (Revista CEFAC, 2020)
ABSTRACT Purpose: to characterize school-aged patients with persistent stuttering regarding their self-reported experiences of violence at school. Methods: the sample comprised 10 patients with persistent stuttering, 10 to 17 years old, regardless of their sex and stuttering characteristics, who received care at a fluency outpatient center in the heart of São Paulo State, Brazil. The collection instrument was an 11-question, multiple-choice, self-administered questionnaire. The data were descriptively analyzed based on the frequency of the answers. Results: almost half of the stuttering patients reported suffering bullying, in which they were given nicknames, defamed, blamed for everything that happened, physically attacked, and mocked. The classroom was the most mentioned environment where bullying took place. The following reactions to violence were mentioned: “talking to friends, teachers/principals, and relatives”, “sadness”, and “desire to change schools”. Conclusion: despite the small sample size, it was possible to note alarming data and the importance of educative/preventive actions in the school environment, approaching both bullying and stuttering.